Pengembangan Lembar Kegiatan Siswa (LKS) Bangun Ruang Sisi Datar Berbasis PBL - Sulistyani, Niluh (Jurnal Matematika; Vol 6 No 1 (2016), 2016)
Quality of learning mathematics is supported by the availability of qualified learning facilities for students, for example worksheet. This study aims to describe how to develop and produce student’s worksheet (LKS) of flat side space, based on Problem-Based Learning (PBL) which is valid and practical. This study is research and development which is held in SMP N 2 Pengasih, Yogyakarta using Thiagarajan development model. The result of study is obtained development process of LKS comprising defining phase, designing phase, developing phase that starts from expert validation, revision, readability test, product revision, field test, and ends with the disseminating phase. The result of expert validation shows that LKS is valid in very good category. LKS practically gets very good category from tehacher assessment. The result of students assessment shows that 43,75% students can use LKS in very good category and 56,25% students can use LKS in good category.
Keywords: development; student’s worksheet (LKS); flat side space; Problem-Based Learning; PBL